Systematic Literature Review: Penggunaan Media Puzzle terhadap Pemahaman Konsep IPS pada Siswa Sekolah Dasar - Bagar Arifin; Dewi Permoni; Mega Ayu Putri Hapsari; Siti Nur Elisa; Fina Fakhriyah; Erik Aditia Ismaya (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This study aims to conduct a literature review related to the use of puzzle media to understand social studies concepts in elementary school students. This study used the Sytematic Literature Review (SLR) Method by searching 200 articles for keyword understanding concepts, social studies, elementary schools in Publish or Perish 8 (POP) with a time span from 2018 – 2023. Furthermore, there were only 15 articles resulting from the selection and deletion of articles that were not appropriate or relevant to the keyword. From the results of this SLR, it shows that the use of media such as puzzles can affect the understanding of social studies concepts of elementary school students. With innovative, interactive learning can generate motivation and stimulation of elementary school students' learning activities so that children understand faster and are excited to participate in learning activities in class.